Improving ACGME Compliance for Obstetric Anesthesiology Fellows Using an Automated Email Notification System - Ende, Holly B.; Richardson, Michael G.; Lopez, Brandon M.; Wanderer, Jonathan P. (Applied Clinical Informatics, 2021)
Background The Accreditation Council for Graduate Medical Education establishes minimum case requirements for trainees. In the subspecialty of obstetric anesthesiology, requirements for fellow participation in nonobstetric antenatal procedures pose a particular challenge due to the physical location remote from labor and delivery and frequent last-minute scheduling.Objectives In response to this challenge, we implemented an informatics-based notification system, with the aim of increasing fellow participation in nonobstetric antenatal surgeries.Methods In December 2014 an automated email notification system to inform obstetric anesthesiology fellows of scheduled nonobstetric surgeries in pregnant patients was initiated. Cases were identified via daily automated query of the preoperative evaluation database looking for structured documentation of current pregnancy. Information on flagged cases including patient medical record number, operating room location, and date and time of procedure were communicated to fellows via automated email daily. Median fellow participation in nonobstetric antenatal procedures per quarter before and after implementation were compared using an exact Wilcoxon-Mann-Whitney test due to low baseline absolute counts. The fraction of antenatal cases representing nonobstetric procedures completed by fellows before and after implementation was compared using a Fisher's exact test.Results The number of nonobstetric antenatal cases logged by fellows per quarter increased significantly following implementation, from median 0[0,1] to 3[1,6] cases/quarter (p = 0.007). Additionally, nonobstetric antenatal cases completed by fellows as a percentage of total antenatal cases completed increased from 14% in preimplementation years to 52% in postimplementation years (p < 0.001).Conclusion Through an automated email system to identify nonobstetric antenatal procedures in pregnant patients, we were able to increase the number of these cases completed by fellows during 3 years following implementation.
Keywords: anesthesiology; education; educational needs; obstetrics/gynecology; surgical and anesthesia information systems